Karien, Türkei. Zur Reflexion der ptolemäischen Herrschaft in der karischen Münzprägung. Die Arbeiten des Jahres 2020 - Vidin, Hülya (e-Forschungsberichte des DAI, 2022)
Beside other Hellenistic hegemonies the Ptolemies ruled over Caria from the end of the 4th until the late 3rd century BC. The Carian domain of the Ptolemies extended from the islands opposite the Carian mainland along the Carian coast and to some cities in the Western inland. The seven cities of Iasos, Mylasa, Halikarnassos, Knidos, Kaunos, Kos and Kalymnos in the Ptolemaic sphere of influence minted coins during their rule in the 3rd century BC. As part of a three-month research project, the coins of these cities were examined to determine whether Ptolemaic coinage had an influence on Carian civic coinage from an iconographic and metrological perspective and whether the cities used the coins as a medium to communicate their loyalty to the Ptolemaic royal house.